2020
DOI: 10.3390/info11050265
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Considerations Concerning Motion Sickness Investigations during Automated Driving

Abstract: Automated driving vehicles will allow all occupants to spend their time with various non-driving related tasks like relaxing, working, or reading during the journey. However, a significant percentage of people is susceptible to motion sickness, which limits the comfort of engaging in those tasks during automated driving. Therefore, it is necessary to investigate the phenomenon of motion sickness during automated driving and to develop countermeasures. As most existing studies concerning motion sickness are fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 52 publications
3
26
1
Order By: Relevance
“…The fifth paper "Methodological Considerations Concerning Motion Sickness Investigations during Automated Driving" by Mühlbacher, Tomzig, Reinmüller and Rittger [17] discusses methodological aspects for investigating motion sickness in the context of automated driving including measurement tools, test environments, sample, and ethical restrictions. Additionally, methodological considerations guided by different underlying research questions and hypotheses are provided.…”
Section: Evaluating the Influence Of Driver State Driver Availabilitmentioning
confidence: 99%
“…The fifth paper "Methodological Considerations Concerning Motion Sickness Investigations during Automated Driving" by Mühlbacher, Tomzig, Reinmüller and Rittger [17] discusses methodological aspects for investigating motion sickness in the context of automated driving including measurement tools, test environments, sample, and ethical restrictions. Additionally, methodological considerations guided by different underlying research questions and hypotheses are provided.…”
Section: Evaluating the Influence Of Driver State Driver Availabilitmentioning
confidence: 99%
“…With the vehicle taking complete control of the driving process, the drivers’ role is expected to change completely, enabling them to work or entertain themselves throughout the journey. However, it has been shown that engaging in tasks such as reading [ 1 ] or performing visual search tasks [ 2 ] that deprive passengers of a clear view of the external moving environment, can lead to increased motion sickness (MS), introducing a new challenge for autonomous vehicles’ infotainment designs [ 3 , 4 , 5 , 6 ]. Iskander et al have written an extensive review on the new “autonomous car sickness” (i.e., motion sickness, perceived in autonomous vehicles) in comparison to classic “car sickness” [ 4 ], expressing the need to separately study MS in AVs.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used subjective methods for assessing MS in vehicles include the Motion Sickness Questionnaire (MSQ) [ 16 , 17 ] or its derivative—Simulator Sickness Questionnaire (SSQ) [ 18 ] for detailed overall evaluation of MS, Fast Motion Sickness Scale (FMS) [ 19 ] for faster multiple evaluations during the study trials and Motion Sickness Susceptibility Questionnaire (MSSQ) [ 20 ] or Georgia Tech Simulator Sickness Screening Protocol Paper (GTSSSP) [ 21 ] for screening drivers’ susceptibility to MS. Some researchers also use separate Likert scales to assess different aspects of MS [ 5 ]. Subjective MS effects identified with subjective assessments are usually collected post-trial and provide an overall score.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations